Digital workers' stress: The role of digital creativity in the future jobs - Ludovico Bullini Orlandi; Jasna Pocek; Sascha Kraus; Alessandro Zardini; Cecilia Rossignoli (Journal of Innovation & Knowledge (JIK), 2024)
The relationship between remote work and employee well-being represents a longstanding debate in the management literature, and it has been rekindled by the remote work adoption forced by COVID-19 lockdowns. Previous literature has shown that remote working can enhance flexibility and work-life balance under certain conditions. However, it can also be a source of increased stress, burnout, and greater work-to-family conflicts. The adverse effects are particularly relevant when remote work adoption is imposed by external conditions for both employees willing to adopt it and those who feel less comfortable with it. This study contributes to the debate by surveying 471 employees 'forced' into remote work adoption because of COVID-19 lockdowns and by pinpointing three individual-level job resources that can affect stress in such a context. In particular, it shows that 'future of work' job components are not a source of stress, as suggested by recent research, but a critical antecedent of remote working self-efficacy and a source of creativity in leveraging digital technologies in such a context.
Keywords: M00; M10; M12; 650; Digital creativity; Future of work; Remote work; Remote work self-efficacy; Remote work stress